Biogenic amines in the testis: Sources, receptors and actions - Frungieri, Monica Beatriz (2024)
Biogenic amines are signaling molecules with multiple roles in the centralnervous system and in peripheral organs, including the gonads. A series ofstudies indicated that these molecules, their biosynthetic enzymes and theirreceptors are present in the testis and that they are involved in the regulation ofmale reproductive physiology and/or pathology. This mini-review aims tosummarize the current knowledge in this field and to pinpoint existingresearch gaps. We suggest that the widespread clinical use of pharmacologicalagonists/antagonists of these signaling molecules, calls for new investigations inthis area. They are necessary to evaluate the relevance of biogenic amines forhuman male fertility and infertility, as well as the potential value of at least one ofthem as an anti-aging compound in the testis.